2022
DOI: 10.18502/jthc.v17i2.9839
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of 1-Year Major Cardiovascular Events after ST-Elevation Myocardial Infarction in a Specialized Cardiovascular Center in Western Iran

Abstract: Background: Identifying the long-term predictors of recurrent cardiovascular events may help improve the quality of care and prevent subsequent events. We aimed to investigate the predictors of 1-year major cardiovascular events (MACE) in patients discharged after ST-elevation myocardial infarction (STEMI) in a tertiary hospital in Iran. Methods: This registry-based cohort study included consecutive STEMI patients between 2016 and 2019 in Imam-Ali Hospital, Kermanshah, Iran. All patients discharged alive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(51 reference statements)
0
1
1
Order By: Relevance
“…Ejection fraction proved to be an independent predictor of MACE events. 43 However, in our results, there was no significant difference in ejection fraction between the two groups of patients. The possible reasons are as follows: 1) The time from onset to admission was short, and the cardiac function was not seriously impaired; 2) Patients with hemodynamic instability have been excluded.…”
Section: Discussioncontrasting
confidence: 70%
“…Ejection fraction proved to be an independent predictor of MACE events. 43 However, in our results, there was no significant difference in ejection fraction between the two groups of patients. The possible reasons are as follows: 1) The time from onset to admission was short, and the cardiac function was not seriously impaired; 2) Patients with hemodynamic instability have been excluded.…”
Section: Discussioncontrasting
confidence: 70%
“… 4 STEMI-surviving patients are at serious risk for recurrent coronary artery disease after discharge because of the chronic process of the blockage of a major artery. 5 The readmission rate is an important indicator in evaluating the efficacy of healthcare systems and the preventive and sanitary steps to avoid such events. Recent studies have reported that approximately 20% of patients have unplanned readmission within 30 days of discharge, with an estimated direct cost of $US 1 billion to healthcare systems annually.…”
Section: Introductionmentioning
confidence: 99%